Problem-Based Learning in Fiqh Instruction: A Qualitative Study on the Development of Critical Thinking and Religious Character - Muhamad Ansori (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
Fiqh instruction in Islamic senior secondary schools must connect Islamic legal knowledge with students’ capacity to reason contextually and enact religious values in contemporary life. This study examined how Problem-Based Learning (PBL) was implemented in Fiqh instruction, what forms of critical reasoning students manifested, and how religious-character values were enacted during classroom participation. A qualitative case study was conducted at Madrasah Aliyah Al-Qodiri 1 Jember from January to March 2025. Participants comprised three selected Fiqh teachers and fifteen students representing varied achievement levels. Data were generated through semi-structured interviews, participant observation, and analysis of lesson plans, problem scenarios, and student work. Analysis combined the interactive processes of data condensation, data display, and conclusion verification with thematic coding. Credibility was supported through data triangulation, member checking, reflexive notes, and an audit trail. The findings showed that PBL was enacted through problem orientation, collaborative investigation, evidence-based reasoning, presentation, and reflection. Authentic cases involving digital transactions, contemporary worship, and social-religious dilemmas created opportunities for students to clarify legal issues, connect dalil with context, construct arguments, and review conclusions. Responsibility, honesty, tolerance, and cooperation were manifested through task completion, acknowledgment of argumentative limitations, respectful disagreement, and collaborative case resolution. The study’s originality lies in conceptualizing these interconnected processes as contextual jurisprudential literacy, rather than treating critical thinking and religious character as separate outcomes. This study contributes a contextually grounded explanation of how facilitated PBL can connect normative Islamic sources, critical reasoning, and ethical classroom participation. It also offers practical guidance for designing authentic problems, differentiated scaffolding, dialogical facilitation, and reflective Fiqh instruction while avoiding unsupported causal claims about measured improvement or permanent character internalization.